The effective manager - Andres, Tomas Quintin D. (Quezon City New Day Publishers of the Christian Literature Society of the Philippines, 1995)
A distillation of the best management theories and practices, this book was written to teach, integrate, and infuse the proper knowledge, attitudes, skills, habits and values to all people who will be managing people to attain organizational, national as well as personal objectives.
"These books have been written to teach, integrate, and in fuse the people knowledge, attitudes, skills, habits, and values (KASHAV) to all present and future people who will be managing people to attain organizational, national, as well as personal and family objectives. It contains hundred of ideas, techniques, strategies and insights on how to improve business and management know-how. This book is intended for individual use as well as textbook in management source, administration and supervision, leadership and other related subjects."
Keywords: Management -- Handbooks, manuals, etc